Analisis Wacana Politik Debat Publik Calon Presiden dan Calon Wakil Presiden Republik Indonesia - Farid Iskandar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study discusses to examine the phenomenon of political communication during the presidential and vice-presidential elections in 2019. From cases that occur during the campaign period, there are often symptoms of lack of argumentation, lack of credibility, and lack of ability to communicate through debate. This research uses The Functional Debate Campaign theory stated by William, L. Benoit. It is including the use of research methods and analytical techniques developed by Benoit. From the results of this study it is known that all candidates for President and Vice President mostly direct their political discourse into policy rather than turn up their characters, but in conveying their political messages still have shortcomings from verbal and nonverbal aspects. Whereas in terms of functional strategy it is considered to be sufficient because it has used several techniques, but it has not been evenly displayed by all candidates. There is also a weakness that appears in all candidates seen from the debate strategy which is less able to build good acclaim to build election by candidates by trying to attack and defend when attacked. The implications of the research on this candidate's debate, show that the use of candidate debates on television as a political communication forum was attracted the media and voters, however, it has not yet an ideal primary means for voters to see the credibility and capability of the prospective leader.